1974
DOI: 10.1007/bf00123463
|View full text |Cite
|
Sign up to set email alerts
|

Teaching methods and student personality ? The search for an elusive interaction

Abstract: Decades of research at the tertiary level have produced the finding that the use of different teaching methods makes no difference to student learning when end-ofcourse examination performance is accepted as the criterion of such learning. This conclusion has been based on a comparison between the average mark gained by groups of subjects taught in different ways. The present article takes the position that the use of such mean scores serves to conceal individual variability, and hypothesizes that it is possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1975
1975
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Teachercentered instruction probably provides more task orientation than does student-centered instruction. Thus Dowaliby and Schumer's (1973) finding that teacher-centered instruction optimizes learning for high-anxious students fits with Sarason's results, as does Stanton's (1974) finding that anxious students perform better with lecture than with independent study.…”
Section: Helping the Anxious Studentsupporting
confidence: 66%
“…Teachercentered instruction probably provides more task orientation than does student-centered instruction. Thus Dowaliby and Schumer's (1973) finding that teacher-centered instruction optimizes learning for high-anxious students fits with Sarason's results, as does Stanton's (1974) finding that anxious students perform better with lecture than with independent study.…”
Section: Helping the Anxious Studentsupporting
confidence: 66%
“…Theoretical and research literature that discusses personality and learning has been done for almost a century [26]. Among the results in this century was the findings of Stanton in 1974 that students tend to do better under the teaching method, the latter seeing themselves as more tense and anxious than students tending to perform better under the previous method [27]. Next research by Murray and his colleagues in 1990 studied 29 personality traits of teachers in learning at university, among the results were specific personality traits that contributed to effective teaching that were significantly different for different types of courses [28].…”
Section: Literature Review 21 the Urgency Of The Teacher's Personality Competencementioning
confidence: 99%
“…[ 65 ], who repeated it, and [ 66 ], who did the same. On the other hand, these latter reviewers expressed optimism that research will be more fruitful shortly [ 67 ]. further claims that no significant difference in exam performance was detected between students taught through a lecture approach and those oriented through a guided reading method in his study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…When no significant association was established between a student's choice of teaching technique and his examination performance after being taught by that approach, according to Ref. [ 67 ], Stanton confirmed that the “no difference” in results from different teaching approaches could be due to crude measurement devices that were unable to identify the true which genuinely exists. Despite this, certain features can distinguish students who prefer to learn through lectures and those who like to learn through guided reading [ 67 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation